You have not said WHAT to do. You need to know where you're going or it's unlikely you'll get there.

If you put the given numbers in the given expression, you have

-31 = 17 + (n-1)(-4)

You can solve this for n if that is useful.

-48 = (n-1)(-4) (subtract 17)

12 = n - 1 (divide by -4)

13 = n (add 1)

The 13th term of the series is -31.

If you put the given numbers in the given expression, you have

-31 = 17 + (n-1)(-4)

You can solve this for n if that is useful.

-48 = (n-1)(-4) (subtract 17)

12 = n - 1 (divide by -4)

13 = n (add 1)

The 13th term of the series is -31.